The Fate of Chemical Pollutants with Soil Properties and Processes in the Climate Change Paradigm—A Review - Biswas, Bhabananda; Qi, Fangjie; Biswas, Jayanta Kumar; Wijayawardena, Ayanka; Khan, Muhammad Atikul Islam; Naidu, Ravi (Soil systems, 2018)
Heavy metal(loid)s and organic contaminants are two major groups of pollutants in soils. The fate and exposure of such pollutants in soil depends on their chemical properties, speciation, and soil properties. Soil properties and processes that control the toxicological aspects of pollutants include temperature, moisture, organic matter, mineral fractions, and microbial activities. These processes are vulnerable to climate change associated with global warming, including increased incidences of extreme rainfall, extended dry periods, soil erosion, and a rise in sea level. Here we explain evidence that relates to the effects of climate change-driven soil processes on the mobility, transport, and storage of pollutants in soil. The review found that changes in climate could increase human exposure to soil contaminants mainly due to processes involving soil organic carbon (SOC), surface runoff, redox state, and microbial community. However, uncertainties remain in relation to the extent of contaminant toxicity to human health, which is linked to global change drivers.